Isotopic niches of juvenile and adult green turtles (Chelonia mydas) in feeding and nesting areas in Brazil, southwestern Atlantic Ocean - Fernandes, Amanda; Bugoni, Leandro; Bianchini, Adalto; Zapelini, Cleverson; Schiavetti, Alexandre (Frontiers in Marine Science, 2023)
Stable isotope analysis is an approach that allows inferring feeding ecology and trophic structure of populations, especially for species that are difficult to observe in natural habitats, such as marine turtles. This study investigated the niche breadth of adult and juvenile green sea turtles (Chelonia mydas) through δ15N and δ13C values in carapace scutes. During 2017 and 2018, tissues were collected from juveniles in a feeding area in southeastern Brazil (n = 60) and from adults in a nesting area in northeastern Brazil, at Fernando de Noronha (n = 21). Our results revealed no temporal variations in the isotopic values of adult green turtles and the mean δ15N values are compatible with the isotopic values of primarily herbivorous animals. In southeastern Brazil, the δ13C values and isotopic niche breadth differences observed in juvenile green turtles suggest that variations in habitat (i.e., channel between the municipalities of Ilhabela and São Sebastião - “SSC” and region comprising the other two municipalities of Ubatuba and Caraguatatuba - “CAU”, as defined in this study based on oceanographic current dynamics) can influence their isotopic niche. The isotopic values observed in juvenile green turtles demonstrated a high degree of feeding behavior plasticity and individual variability, which were possibly influenced by the dynamic of oceanographic currents and seasonal nutrient inputs. These findings help to elucidate the feeding behavior of green turtles at different life stages and the potential influence of oceanographic current dynamics in key feeding sites for juvenile green turtles.